Exploring the Lived Experiences of Gender Dysphoric Individuals - Noor, Hafsa; Farooq, Ayesha (Annals of Human and Social Sciences, 2025)
This study aims to explore the lived experiences of gender dysphoric individuals, focusing on the formation of their identity under the influence of family, media, and peer group. This study provides insight into how an individual’s identity is transformed, particularly in terms of self-expression and self-discovery. Despite growing advocacy and recognition, the lived experiences remain poorly understood, especially in Pakistan. Through in-depth interviews and qualitative approach, this research provides a platform for gender dysphoric individuals to share their stories of self-discovery. The findings highlight the significant influence of family, role models, and media. To address this, solutions include increasing awareness through education and regulating media content.